Streptolysin S targets the sodium-bicarbonate cotransporter NBCn1 to induce inflammation and cytotoxicity in human keratinocytes during Group A Streptococcal infection - Hammers, Daniel E.; Donahue, Deborah L.; Tucker, Zachary D.; Ashfeld, Brandon L.; Ploplis, Victoria A.; Castellino, Francis J.; Lee, Shaun W. (Frontiers in Cellular and Infection Microbiology, 2022)
Group A Streptococcus (GAS, Streptococcus pyogenes) is a Gram-positive human pathogen that employs several secreted and surface-bound virulence factors to manipulate its environment, allowing it to cause a variety of disease outcomes. One such virulence factor is Streptolysin S (SLS), a ribosomally-produced peptide toxin that undergoes extensive post-translational modifications. The activity of SLS has been studied for over 100 years owing to its rapid and potent ability to lyse red blood cells, and the toxin has been shown to play a major role in GAS virulence in vivo. We have previously demonstrated that SLS induces hemolysis by targeting the chloride-bicarbonate exchanger Band 3 in erythrocytes, indicating that SLS is capable of targeting host proteins to promote cell lysis. However, the possibility that SLS has additional protein targets in other cell types, such as keratinocytes, has not been explored. Here, we use bioinformatics analysis and chemical inhibition studies to demonstrate that SLS targets the electroneutral sodium-bicarbonate cotransporter NBCn1 in keratinocytes during GAS infection. SLS induces NF-κB activation and host cytotoxicity in human keratinocytes, and these processes can be mitigated by treating keratinocytes with the sodium-bicarbonate cotransport inhibitor S0859. Furthermore, treating keratinocytes with SLS disrupts the ability of host cells to regulate their intracellular pH, and this can be monitored in real time using the pH-sensitive dye pHrodo Red AM in live imaging studies. These results demonstrate that SLS is a multifunctional bacterial toxin that GAS uses in numerous context-dependent ways to promote host cell cytotoxicity and increase disease severity. Studies to elucidate additional host targets of SLS have the potential to impact the development of therapeutics for severe GAS infections.